Regional Autonomy Implementation through Improvements Quality of Governance, and Public Services - Widodo, Sugeng (American Journal of Social Sciences and Humanities, 2019)
Indonesia is one of the countries implementing regional decentralization and autonomy. The Central Government has provided a large enough allocation of village funds for local governments with the aim of improving the quality of public services. As with laws and regulations, the allocation of funds provided is expected to increase productivity and empowerment of human resources and provide service satisfaction to the community. Based on the study of literature, it was revealed that problems arise in the form of obstacles and challenges that roll along the acceleration of local government programs in an effort to optimize public services. The implementation of regional autonomy through improving the quality of governance and public services aims at people’s welfare. The results of the study mentioned that the public requires maximum public service both psychologically and in physical form. In addition, it is important to carry out modern reforms and acceleration so that public services can be maximized.